Evaluation of mastic in bituminous mixtures - Silva, Hugo Manuel Ribeiro Dias da (2002)
The efficiency of the asphalt-aggregate bond is one of the key factors which affects the mechanical resistance of bituminous mixtures and a better understanding of its performance allows the behaviour of mixture to be more accurately predicted. The asphalt-aggregate bond depends on the properties of the mastic and the mixture of fine aggregate and bitumen which bonds itself to the larger sized particles within the bituminous mixture. This mastic plays an im-portant role in the asphalt-aggregate bond because failure occurs in this part of the bituminous mixture. For the development of an adhesion test (at the University of Minho), a study was conducted to evaluate the mastic part of bituminous mixtures. A physical evaluation of the mastic was performed by sieve analysis. The material retained on each sieve was characterized by evaluating the binder content and the gradation of the fine aggregate fraction. The results of this study allow the mastic part of a given mixture to be characterised as a function of aggregate gradation and binder content. The reverse process, where the type of mixture is defined by knowing the mas-tic, is also being studied, but this is not an easy process and it only allows some mixture variables to be defined.